Increasing Environmental Awareness Through the Implementation of the Adiwiyata Mandiri Program at SMAN 1 Sukakarya - Dewi Dewi Murwanti Khasanah; Siti Zulaikha siti; Heru Santosa heru (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the implementation of the Adiwiyata Mandiri Program in increasing students' environmental awareness at SMAN 1 Sukakarya. Increasingly complex environmental issues demand effective environmental education at the secondary school level. This study uses a qualitative method with a case study approach. Data was collected through observation, in-depth interviews, and documentation over a period of 6 months. The research subjects include students, teachers, and managers of the Adiwiyata program. The results of the study showed that the implementation of the Adiwiyata Mandiri Program succeeded in increasing students' environmental awareness by 78% based on pre-test and post-test. Success indicators include increased participation in environmental activities, changes in environmentally friendly behaviors, and understanding of sustainable development concepts. The main supporting factors are the school's commitment, teacher support, and active student participation. The obstacles faced include limited funds, lack of awareness among some school residents, and lack of infrastructure support. Research recommendations include increasing funding allocation, strengthening teacher training programs, and optimizing the role of school committees.